2015
DOI: 10.1248/bpb.b15-00410
|View full text |Cite
|
Sign up to set email alerts
|

Antimelanogenic Effects of Picrionoside A Isolated from the Leaves of Korean Ginseng

Abstract: This study was initiated to isolate active metabolites from the leaves of Panax ginseng. Among them, picrionoside A, a megastigmane glucoside, was isolated from the leaves of P. ginseng C. A. MEYER and its chemical structure was determined based on spectroscopic methods, including FAB-MS, one-dimensional (1D)-NMR, 2D-NMR, and IR spectroscopy. Picrionoside A from P. ginseng has not been investigated previously, and its biological or pharmaceutical activities have not been reported elsewhere. The IC 50 value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In recent years, it not only is used for its effect on the skin, but is also clearly a scientific approach for the treatment of various diseases [23] , [24] . It has been reported that several ginsenosides and cinnamic acid are inhibitory agents of melanogenesis, and are found mainly in P. ginseng [11] , [25] , [26] . Therefore, we studied the expression of a protein found in melanin synthesis by nontoxic FGA (it has not been studied with respect to the physiological activities, as mentioned in the introduction) in melan-a cells.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it not only is used for its effect on the skin, but is also clearly a scientific approach for the treatment of various diseases [23] , [24] . It has been reported that several ginsenosides and cinnamic acid are inhibitory agents of melanogenesis, and are found mainly in P. ginseng [11] , [25] , [26] . Therefore, we studied the expression of a protein found in melanin synthesis by nontoxic FGA (it has not been studied with respect to the physiological activities, as mentioned in the introduction) in melan-a cells.…”
Section: Resultsmentioning
confidence: 99%
“… Chemical structure of miscellaneous tyrosinase inhibitors, 44a – 44c , 128 4 5 129 46a – 46c, 130 47a – 47c, 131 48a – 48b , 132 49 133 50 135 51a – 51e 136 and 52 . 139 .…”
Section: Miscellaneous Mushroom Tyrosinase Inhibitorsmentioning
confidence: 99%
“…Melanoma cell lines were normally grown in medium such as McCoy’s 5A, Dulbecco’s modified Eagle’s medium (DMEM), Ham’s F12/DMEM, Ham’s F12, DMEM, MEM, or RPMI‐1640 . In particular, DMEM with high glucose content is more preferable for growth of B16 cell lines and melanin synthesis than other media .…”
Section: Protocol and Assaysmentioning
confidence: 99%
“…McCoy's 5A, Dulbecco's modified Eagle's medium (DMEM), Ham's F12/DMEM, Ham's F12, DMEM, MEM, or RPMI-1640. 70,74,109,111,118 In particular, DMEM with high glucose content is more preferable for growth of B16 cell lines and melanin synthesis than other media. 7 High glucose media may provide sufficient energy in a form of ATP to support fast cell proliferation of melanoma cell line.…”
Section: Medium Compositionmentioning
confidence: 99%